2014
DOI: 10.1093/jnci/dju331
|View full text |Cite
|
Sign up to set email alerts
|

Use and Misuse of Waterfall Plots

Abstract: Waterfall plots are subject to substantial variability in criteria used to define them and are influenced by measurement errors; they should be generated by trained radiologists. Caution should be exercised when interpreting results of waterfall plots in the context of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The first is that in contrast with OS, where the date of death is precise and can be ascertained for all patients, surrogates are prone to reader interpretation, measurement error, evaluation bias, and attrition bias. 65,66 These artifacts may create spurious surrogate benefits. The second explanation is a biological one: a cancer drug with favorable surrogate effects may affect changes in tumor growth or aggressiveness or may increase off-target deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that in contrast with OS, where the date of death is precise and can be ascertained for all patients, surrogates are prone to reader interpretation, measurement error, evaluation bias, and attrition bias. 65,66 These artifacts may create spurious surrogate benefits. The second explanation is a biological one: a cancer drug with favorable surrogate effects may affect changes in tumor growth or aggressiveness or may increase off-target deaths.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In addition, medical oncologists with limited training in imaging or application of imaging criteria may have high interobserver variability in their assessment compared with other oncologists and radiologists. 31 These alternate workflows for response assessment may lead to inefficiency, high variability, and low interreader agreement. The role of a single IA per trial can serve as a catalyst in the relationship between radiologists, oncologists, and clinical staff, enabling improved reliability, decreased interreader variability, and faster turnaround time without experimenter bias.…”
Section: Discussionmentioning
confidence: 99%
“…27,29,30 However, medical oncologists are often inadequately trained for both imaging assessment and the application of study-specific response evaluation criteria, and prior studies have shown high interobserver variability. 31 In addition, there is a potential for introduction of evaluation or experimenter bias in the assessment due to patient-provider relationship and knowledge of the treatment arm and clinical course. 32,33 At the University of Michigan Rogel Cancer Center, medical oncologists were previously burdened with response assessment.…”
Section: Introductionmentioning
confidence: 99%
“…criteria used to define them and found that they are influenced by interobserver measurement errors of tumor size. They recommended that waterfall plots should be generated only after central review of imaging by radiologists trained in Response Evaluation Criteria in Solid Tumours 1.1 (RECIST) measurement (31). Waterfall plots depict only the best on-study change in tumor burden relative to baseline for each individual patient and cannot represent the kinetics or dynamics of tumor growth (32).…”
Section: Waterfall Plotsmentioning
confidence: 99%